Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s41999-019-00174-4
|View full text |Cite
|
Sign up to set email alerts
|

The recent secular trend in grip strength among older adults: findings from the English Longitudinal Study of Ageing

Abstract: Aim Our aim was to investigate whether there has been a recent secular trend in the grip strength of older English adults, using data from the English Longitudinal Study of Ageing (ELSA). Findings We found evidence of a slight decline in mean grip strength between 2004 and 2013. This decline is equivalent to 65-year-olds' mean strength declining to that previously seen in individuals at age 69, and did not appear to be explained by differences in lifestyle risk factors. Message These findings are important sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…While few studies have examined temporal trends in HGS for older adults, in contrast to our findings, recent trends are mixed, indicating a decline in the HGS of older Canadian [14], English [15], and Central European [16] adults, and an improvement in older Northern and Southern European [16] adults. Surprisingly, declines in HGS for older Canadian [14] and English [15] adults have coincided with increases in body size (i.e., body mass index), suggesting that declines in other factors (e.g., habitual physical activity levels) may be involved. However, the recent decline in mean HGS for older English adults was independent of trends in body size and selfreported physical activity levels, as well as other confounders such as socioeconomic position and smoking history [15].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…While few studies have examined temporal trends in HGS for older adults, in contrast to our findings, recent trends are mixed, indicating a decline in the HGS of older Canadian [14], English [15], and Central European [16] adults, and an improvement in older Northern and Southern European [16] adults. Surprisingly, declines in HGS for older Canadian [14] and English [15] adults have coincided with increases in body size (i.e., body mass index), suggesting that declines in other factors (e.g., habitual physical activity levels) may be involved. However, the recent decline in mean HGS for older English adults was independent of trends in body size and selfreported physical activity levels, as well as other confounders such as socioeconomic position and smoking history [15].…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, declines in HGS for older Canadian [14] and English [15] adults have coincided with increases in body size (i.e., body mass index), suggesting that declines in other factors (e.g., habitual physical activity levels) may be involved. However, the recent decline in mean HGS for older English adults was independent of trends in body size and selfreported physical activity levels, as well as other confounders such as socioeconomic position and smoking history [15]. Although trends in body size and physical activity levels were not directly examined in this study, it appears as though the improvement in HGS observed in older Japanese adults has, as expected, corresponded to increases in body size and exercise/sport participation [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grip strength: Grip strength is included in cohort studies as a measure of upper body strength and it was tested using a gripometer in all respondents for whom it was safe, for example, those without swelling, pain, or recent injury. Three values were recorded for each hand, using a Smedley dynamometer in a standing position, starting with the nondominant hand and alternating between hands and the maximum value for the dominant hand was used in the analysis (19,20).…”
Section: Physical Performance Assessments Short Physical Performance Battery (Balance Tests Chair Rises Gait Speed)mentioning
confidence: 99%